The effect of Trigonella foenum‐graecum extract on prostate‐specific antigen, and prostate function in otherwise healthy men with benign prostate hyperplasia. (11th December 2019) - Rao, Amanda; Grant, Ross
Abstract : The aim of this trial was to evaluate the effect of a standardised Trigonella foenum‐graecum (Fenugreek) extract on the symptoms of benign prostate hyperplasia (BPH) using a double‐blind randomised placebo controlled design. The study recruited 100 healthy males aged between 45 and 80 years with symptoms of BPH who recorded a minimum score of eight on the International Prostate Symptom Score. Participants were randomised to an oral dose of either 600mg Trigonella foenum‐graceum per day or placebo for 12 weeks. The primary outcome measure was the International Prostate Symptom Score total and subdomain scores. The secondary outcomes were serum levels of the hormones (testosterone, free testosterone, and sex hormone binding globulin) prostate‐specific antigen, and safety markers. The results indicated that Trigonella foenum‐graceum did not have an effect on improving the symptoms of BPH. Hormone levels, safety markers, and prostate‐specific antigen remained unchanged and within normal limits after 12 weeks, which adds to the safety profile of this specialised extract.